Effect of Check Dam on Sediment Load Under Vegetation Restoration in the Hekou-Longmen Region of the Yellow River - Zhang, Zeyu; Chai, Junrui; Li, Zhanbin; Chen, Li; Yu, Kunxia; Yang, Zhi; Zhang, Xia; Zhao, Yang (Frontiers in Environmental Science, 2022)
With years of vegetation restoration and check dam construction on the Loess Plateau, the sediment load of the middle reaches of the Yellow River have decreased sharply; however, the effects of check dam on this decrease of sediment load with such extensive vegetation restoration remains unclear. In order to further clarify the effects of check dam on sediment load reduction under vegetation restoration, we calculated vegetation coverage and check dam index based on multi-source remote sensing data, and calculated sediment reduction rate caused by human activities by Mann-Kendall statistical test and double cumulative curve, then established regression equations incorporating the check dam index and the sediment reduction rate using data from different geomorphic regions with different vegetation coverages. The results showed that sediment load in the Hekou-Longmen region and its 17 tributaries decreased significantly every year, and the change in sediment load could be divided into 3 typical periods: the base period (P1), the period mainly impacted by check dam construction (P2) and the period with comprehensive impact of check dam construction and vegetation restoration (P3). Compared with sediment load of the tributaries during P1, the sediment load decreased by 60.96% during P2 and by 91.76% during P3. Compared with the contribution of human activities to the reduction in sediment load in P2, the contribution of human activities in P3 increased significantly, while that of precipitation decreased slightly. The sediment reduction effect of check dams is greater in basins with low vegetation coverage than in basins with high vegetation coverage. There are differences in sediment reduction effect of vegetation restorations in different geomorphic regions, and the effect of vegetation restoration alone have certain upper limits. Such as, the upper limit of sediment reduction rate of vegetation restoration for rivers flowing through the sandstorm region is 47.86%. Hence, only combined the construction of check dam with vegetation restoration can it achieve more significant sediment reduction benefit and control soil erosion more effectively.